Role of advanced glycation end products on vascular smooth muscle cells under diabetic atherosclerosis - Mao, Lin; Yin, Ruili; Yang, Longyan; Zhao, Dong (Frontiers in Endocrinology, 2022)
Atherosclerosis (AS) is a chronic inflammatory disease and leading cause of cardiovascular diseases. The progression of AS is a multi-step process leading to high morbidity and mortality. Hyperglycemia, dyslipidemia, advanced glycation end products (AGEs), inflammation and insulin resistance which strictly involved in diabetes are closely related to the pathogenesis of AS. A growing number of studies have linked AGEs to AS. As one of the risk factors of cardiac metabolic diseases, dysfunction of VSMCs plays an important role in AS pathogenesis. AGEs are increased in diabetes, participate in the occurrence and progression of AS through multiple molecular mechanisms of vascular cell injury. As the main functional cells of vascular, vascular smooth muscle cells (VSMCs) play different roles in each stage of atherosclerotic lesions. The interaction between AGEs and receptor for AGEs (RAGE) accelerates AS by affecting the proliferation and migration of VSMCs. In addition, increasing researches have reported that AGEs promote osteogenic transformation and macrophage-like transformation of VSMCs, and affect the progression of AS through other aspects such as autophagy and cell cycle. In this review, we summarize the effect of AGEs on VSMCs in atherosclerotic plaque development and progression. We also discuss the AGEs that link AS and diabetes mellitus, including oxidative stress, inflammation, RAGE ligands, small noncoding RNAs.